Perceived Need and Use of Pain Relief during Labour among Childbearing Women in Akinyele LGA, Ibadan, Nigeria (2015)
Background/Aims: Pain is the most common indication for women during labour. Yet, many women go through labour without any form of pain relief. The objective of this study was to determine the perceived need and use of pain relief during labour among childbearing women in Ibadan, Nigeria. Methods: A cross-sectional study was carried out among 144 women in the Akinyele Area in Ibadan, who were selected using a convenience sampling technique. A structured questionnaire was used to collect data from the women and data were analysed using chi-square testing. Results: The majority of respondents (83.4%) agreed that labour pain is distressing and 58.3% had never used pain relief during labour. Over 60% of women in the study desired pain relief during labour, but 52.8% were not aware they could ask for it. There was a significant association between prenatal pain relief information and use of pain relief (Fisher’s exact test, P<0.00) The perception of labour pain and the need to relieve labour pain were significantly correlated (Fisher’s exact test, P<0.001) Conclusions: Many women desire pain relief during labour; therefore, effort should be made to ensure proper interventions are in place to enable mothers to cope better with labour pain.